Artificial Intelligence in Supply Chain Management: A Bibliometric Analysis of Emerging Trends and Applications - Al-Masa’fah, Wasan (International Review of Management and Marketing, 2026)
This study provides a bibliometric analysis of AI in supply chain management, covering 1998 to early 2025 using Web of Science data. It identifies 302 articles, revealing exponential growth in research output and major contributions from the USA, China, England, Germany, and India, highlighting strong international collaboration. Leading journals like the European Journal of Operational Research and the International Journal of Logistics Management have been pivotal in advancing the field. While technical and operational aspects are well-explored, there’s a notable gap in branding and marketing strategies for AI-driven solutions, indicating a need for consumer-focused studies. Limitations include reliance on one database and potential language bias. Future research should integrate marketing frameworks and consumer behavior analyses. This work serves as a foundational reference for stakeholders aiming to enhance supply chain innovation and resilience through AI.